A critical synthesis of interventions to reduce stigma attached to mental illness - Kenetsoe B. Seroalo; Emmerentia Du Plessis; Magdalena P. Koen; Vicki Koen (AOSIS, 2014)
Background: Interventions have been developed and implemented to reduce the stigma attached to mental illness. However, mental healthcare users are still stigmatised. Objective: The objective of this study was to critically synthesise the best available evidence regarding interventions to reduce stigma attached to mental illness. Method: An exploratory and descriptive research design was followed to identify primary studies; systematic review identifid primary studies answering this research question: What best evidence is available regarding interventions to reduce the stigma attached to mental illness? A search was done on selected electronic databases. Seventeen studies (n = 17) were identifid as providing evidence that answered the research question. The following instruments were used: Critical Appraisal Skills Programme, John Hopkins Nursing Evidence-Based Practice research evidence appraisal tool and the Academy of Nutrition and Dietetics Evidence Analysis Manual. The study was submitted to the Post-graduate Education and Research Committee of the School of Nursing Science at Potchefstroom Campus of North-West University for approval. Results: Results indicated some interventions that reduce the stigma attached to mental illness, such as web-based approaches, printed educational materials, documentary and antistigma fims, as well as live and video performances. Conclusions: Humanising interventions seems to have a positive effect on reducing stigma attached to mental illness. From the results and conclusions recommendations were formulated for nursing practice, nursing education and research. Agtergrond: Ingrypings is ontwikkel en geïmplementeer om die stigma verbonde aan geestesongesteldhede te verminder. Die persone wat aan geestesongesteldhede ly, ondervind egter steeds dat daar 'n stigma aan hulle kleef. Doelstellings: Die doel van die studie was om die beste beskikbare voorbeelde van intervensies om stigmatisering van geestesongesteldhede te verminder, krities saam te vat. Metode: 'n Verkennende en beskrywende navorsingsontwerp is gevolg om primêre studies te identifieer. 'n Sistematiese oorsig is gekies as metode om primêre studies te identifieer om die volgende navorsingsvraag te beantwoord: Wat is die beste beskikbare voorbeelde van ingrypings om die stigma verbonde aan geestesongesteldhede te verminder? 'n Ondersoek is gedoen op 'n uitgesoekte elektroniese databasis. Resultate: Tydens die keuring van studies is 17 studies geïdentifieer (n = 17) as bewyslewering en wat die navorsingsvraag beantwoord. Die volgende instrumente is gebruik: 'Critical Appraisal Skills Programme', 'John Hopkins Nursing Evidence-Based Practice', 'Research Evidence Appraisal Tool and Evidence Analysis Manual', en 'Academy of Nutrition and Dietetics'. Gevolgtrekking: Die studie is aan die Nagraadse Onderrig- en Navorsingskomitee van die Skool van Verpleegkunde van die Potchefstroomkampus, Noordwes-Universiteit, voorgelê vir goedkeuring. Aanbevelings is geformuleer vir die verpleegpraktyk, verpleegonderrig en navorsing.